Light-wave mixing and scattering with quantum gases. (18th March 2015) - Deng, L; Hagley, E W; Zhu, C J
Abstract: We show that optical processes originating from elementary excitations with dominant collective atomic recoil motion in a quantum gas can profoundly change many nonlinear optical processes routinely observed in a normal gas. Not only multi-photon wave mixing processes all become stimulated Raman or hyper-Raman in nature but the usual forward wave-mixing process, which is the most efficient process in normal gases, is strongly reduced by the condensate structure factor. On the other hand, in the backward direction the Bogoliubov dispersion automatically compensates the optical- wave phase mismatch, resulting in efficient backward light field generation that usually is not supported in normal gases.